Enrichment of Rotifera with Lemuru Fish Fermentation on Growth and Survival Rate of Hybrid Grouper Larvae (Epinephelus sp.) - Firmansyah, Muhammad Rizki; Harlim, Renaldo Pratama; Haniah Samara, Syifania; Nurmalia Dewi, Nina (Universitas Airlangga, 2025)
The larvae of the cantang grouper have low survival and slow growth. Efforts to provide good larvae are by providing sufficient nutrition in feed, one of which is by enriching rotifers (Brachionus plicatilis). Rotifera is a zooplankton that contains 40% protein and 13–16% fat. The continuous supply of phytoplankton is difficult for mass production, so the fermentation of lemuru fish can be used as a solution because it contains quite high fat and protein. The purpose of this study is to determine the effect of rotifer enrichment with fermented lemuru fish on the growth and survival of cantang grouper larvae. This study used an experimental method with Completely Randomized Design with five treatments and four replications. The research parameters measured were GR (Growth Rate), SGR (Specific Growth Rate), absolute weight growth, absolute length growth, population growth, rotifer nutrient content test and water quality. The data was analyzed using ANOVA and further tests were carried out Duncan multiple range test. The application of Rotifera enriched by fermentation of lemuru fish had a significantly different effect (p<0.05) on the survival rate and larval growth of cantang grouper, as well as the increase in population and nutrient content of rotifers. The survival rate of cantang grouper larvae was 24%, the GR, SGR, absolute weight growth, and absolute length growth from this study were respectively 1.28 mg/day, 14%/day, 19.22 mg, and 1.93 mm. The growth rate of the Rotifera population increased by 31.2 ind/ml, the nutritional content of protein was 53.12%, and fat was 21.33%.The best dose concentration of enriched Rotifera with fermented lemuru fish is 800 ppm.